A Facile Strategy for Low Young's Modulus PDMS Microbeads Enhanced Flexible Capacitive Pressure Sensors. (24th May 2021) - Sun, Yupeng; Tai, Huiling; Yuan, Zhen; Duan, Zaihua; Huang, Qi; Jiang, Yadong
Abstract: Flexible pressure sensors are widely demanded in human care systems. A simple and effective strategy for sensor fabrication can markedly promote its application. Herein, a facile strategy is employed to prepare a flexible capacitive pressure sensor with a polydimethylsiloxane microbeads‐modified dielectric layer. Owing to the microbeads structure, the proposed sensor achieves a sensitivity of 0.048 kPa −1 in the range of 0–10 kPa with a wide dynamic range (up to 100 kPa). The sensitivity is nine times higher than that of the planar structure. Moreover, the microbeads structured sensor obtains a low limit of detection (0.2 kPa), fast response time (120 ms), and good stability (variation lower than 3.30% after 1000 loading/unloading cycles at 20 kPa). The finite‐elemental analysis reveals that the microbeads structure is critical to enhance the performance of sensors. Finally, the pressure sensor is successfully applied to detect touch signal, joints movement, and breathing, exhibiting its promising prospects as smart wearable devices. Furthermore, the strategy may provide a new idea for the microstructural design of capacitive pressure sensors. Abstract : A strategy to pattern the dielectric layer microstructure of a capacitive pressure sensor with polydimethylsiloxane microbeads is proposed. Owing to this microstructure, the sensitivity of the sensor is nine times higher than that of the planar structure. When worn on the human body, the sensor can respond in real time to the bending angle and speed of human joints.